Accessing Social Support and Overcoming Judgment on Social Media among Parents of Children with Special Needs - Ammari, Tawfiq; Morris, Meredith Ringel; Schoenebeck, Sarita Yardi (Proceedings of ICWSM 2014, 2014)
Over 10 million children are diagnosed with a special need in the United States each year. For their parents, the economic and emotional costs can be overwhelming. Using a mixed methods approach, this research explores how social media supports parents of children with special needs. We find that parents prefer Facebook pages and groups and Yahoo! groups for seeking information and social support. These online sites offer geographic communities for local needs (e.g. school services) and case-based communities for specific conditions (e.g. autism). In terms of judgment, parents perceive online spaces to be less judgmental than offline ones, but these perceptions are nuanced. Specifically, posts on social media about humor, achievement, and treatment suggestions are perceived to be more socially appropriate than posts about judgment, violence, or social comparisons (“one-upping”). These results are the first to show what social media sites special needs parents use and how they experience judgment on these sites. We discuss implications for social media site design and for supporting special needs families.